'For Freedom and Justice': The Responses of Chapels in The Swansea Area to the First World War. (1st December 2017) - Matthews, Gethin
This article explores the responses of Nonconformist chapels in the Swansea area to the First World War, using the rate of recruitment from congregations and the memorialization of the war. Locating the episode in the political- religious rivalry between the Nonconformist denominations and the Established Church, it is clear that one of the motivations for supporting the war effort was the need to be seen to be doing their fair share for King and country at a time when Church disestablishment for Wales was on the statute book. In the discourse in Swansea's newspapers as well as in the chapels themselves, the chapels' Rolls of Honour were visible badges of loyalty.